Analytical Method Development and Validation of Exemestane Tablet by UV Spectrophotometry - S. Angalaparameswari; V. S. Thiruvengadarajan; N. Amruth Kumar; M. Kutumbarao; S. Ramkanth; C. Madhusudhanachetty (E-Journal of Chemistry)
The present research work discusses the development and validation of a UV spectrophotometric method for Exemestane. Simple, accurate and cost efficient spectrophotometric method has been developed for the estimation of Exemestane in Tablet dosage form. The optimum conditions for the analysis of the drug were established. The maximum wavelength (λ max) was found to be 246 nm. The percentage recovery of Exemestane was in the 98.7±0.4. Beers law was obeyed in the concentration range of 2-14 µg/mL. Calibration curves shows a linear relationship between the absorbance and concentration. The line equation y=0.05954x+0.0000 with r2 of 0.9938 was obtained. Validation was performed according to ICH guidelines for Linearity, accuracy, precision, LOD and LOQ. The sample solution was stable up to 36 hours. The proposed method may be suitable for the analysis of Exemestane in tablet formulation for quality control purposes.